Survey Research on the Reading Habits of M.M.S Course Students of University of Mumbai, Studying in Greater Mumbai, Thane, and Navi Mumbai Districts of Maharashtra - Hadvale, B. J. (Prabandhan: Indian Journal of Management, 2011)
This is a Survey Research on the Reading Habits of M.M.S. course Students of University of Mumbai, studying in Greater Mumbai, Thane, and Navi Mumbai districts of Maharashtra. Reading habits play a vital role in the career and life of an individual. This survey was carried out using a structured open ended, multiple choice questionnaire and data was collected from 100 students of 5 management institutes conducting MMS course. Reading habits, for the purpose of this paper, were defined as where, how often, how much, why, and what subjects students read. Finance, marketing, and HR were found to be preferred specialisations. Majority of the students were from commerce, engineering, and science background and had 0 to 2 years of work experience and they had scored 66% marks in their first three semesters of the MMS course. It was found that the respondent students did not have sufficient reading habits. Majority of them merely read for one to two hours in a day. They generally read fictions, novels, comics, sports, adventures, and mysteries more than the text books; and did not read reference books and international news. Students usually prefer to read on the internet and institute’s library. There is apparently no significant relationship between the reading habits and the marks obtained by the students. The students spend maximum time at home, for lectures, travel, and projects. They seem to ignore health, socialisation with friends and relatives. The daily waste of average 2 hours is significant. The respondents have displayed preference for general, case studies, economics, and HR books in the management. The reading on the global issues and business is among the least preferred. For general knowledge, the respondents preferred economics, environment, management, and general news. Politics, technology and entertainment are the least preferred items for general knowledge reading. The respondents have reasonable participation in the committee works at the institutes. About 31% of the respondents do not engage in sports. Large majority of the respondents (76%) have stated that they do read to gain knowledge and awareness. Nonetheless, many of them (31%) read for time pass and relaxation. Home, institute’s library, internet, and during travel are the major places of reading. Many students have reported that they read on the premises of the institute, during lectures, and in canteen. This study has been conducted in the cities of Greater Mumbai, Thane, and Navi Mumbai. Hence, the conclusions may not be valid for the institutes located in rural and semi-urban areas. This study does not cover the students of some of the reputed management institutes like JBIMS, Sydenham, Welingkar. Perhaps, the conclusions may be different with inclusion of those institutes.